IMPROVEMENT ACTIVITY OF ANTIOXIDANT, TYROSINASE INHIBITION, AND ANTI-INFLAMMATORY OF PHALERIA MACROCARPA (SCHEFF.) BOERL) SEED EXTRACTS IN NANOEMULSION DOSAGE FORM: IN VITRO & IN VIVO STUDIES - Agustin, Eriska
Mahkota Dewa seed (Phaleria macrocarpa) has various phytochemical compounds and low pharmacological activities including antioxidants, tyrosinase enzyme inhibition, and antiinflammatory. The production of nanoemulsion preparations is expected to improve the activity of the extract of mahkota dewa seed with ethyl acetate. This study aims to test the mahkota dewa seed nanoemulsion (NE-BMD) against antioxidant activity using the DPPH method, tyrosinase inhibition, and anti-inflammatory using the protein denaturation method with BSA (Bovine Serum Albumin) in vitro. This research is followed by in vivo testing using Wistar white male rats induced by 1% carrageenan for anti-inflammatory activity in selected samples of NE-BMD. The preparation of the NE-BMD was accomplished using the sonication method and followed by selecting two formulation. The formulation contains 3% extract, 1% oleic acid, 12% Cremophor® RH40, and 2% PEG 400. The results of characterization and evaluation of NE-BMD preparations showed that the particle size and polydispersity index were 26.83±1.27 nm (IP: 0.36±0.03) for the F7 formulation and 30.73±1.50 nm (IP: 0.32±0.06) for the F8 formulation. The result of the TEM evaluation showed a spherical globule morphology of the NE-BMD. The antioxidant activity test showed the IC50 value of the BMD extract was 207.01±23.02 ?g/mL, and the NE-BMD F7 and F8 were 15.62±1.40 ?g/mL and 28.39±4.69 ?g/mL, respectively. The testing of tyrosinase enzyme inhibitory activity showed the IC50 values of BMD extract was 938.91±43.98 ?g/mL, NE-BMD preparations F7 and F8 were 587.17±25.36 ?g/mL and 692.79±30.63 ?g/mL, respectively. The protein denaturation testing showed the IC50 values of BMD extract was 401.46±1.01 ?g/mL and NE-BMD preparations F7 and F8 were 94.39±1.24 ?g/mL and 196.63±1.61 ?g/mL. Meanwhile, in vivo anti-inflammatory testing with doses 1 g/kgBW for BMD extract and NE-BMD F7 preparations showed that significantly (p<0.05) improved anti-inflammatory activity compared to single extracts BMD, based on the value of percent protein denaturation inhibition and in vivo test. The results showed that NE-BMD preparations improve several pharmacological activities.